2020
DOI: 10.1002/brb3.1885
|View full text |Cite
|
Sign up to set email alerts
|

Associations between brain‐derived neurotrophic factor and cognitive impairment in panic disorder

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…From our initial database search, 646 records were identified (311 from PubMed, EMBASE, Ovid, and Wiley Online Library and 320 from CNKI, WANFANG DATA, and VIP; 15 more studies were retrieved from related citations). After excluding articles according to the inclusion and exclusion criteria, 25 reports [18][19][20][21][22][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] were included in the qualitative description and the analysis of the distributions of alleles of BDNF Val66Met in patients with stroke. Five repo rts 19,20,22,38,45 including 2089 participants were applied in the meta-analysis to assess the differences in recovery outcomes in patients with stroke having different genotypes (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…From our initial database search, 646 records were identified (311 from PubMed, EMBASE, Ovid, and Wiley Online Library and 320 from CNKI, WANFANG DATA, and VIP; 15 more studies were retrieved from related citations). After excluding articles according to the inclusion and exclusion criteria, 25 reports [18][19][20][21][22][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] were included in the qualitative description and the analysis of the distributions of alleles of BDNF Val66Met in patients with stroke. Five repo rts 19,20,22,38,45 including 2089 participants were applied in the meta-analysis to assess the differences in recovery outcomes in patients with stroke having different genotypes (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Among these, 39 articles were further screened to eliminate duplicated searches. Finally, there were only 11 articles that met the inclusion criteria with available data (Lam et al ., 2004; Shimizu et al ., 2005; Lim et al ., 2007; Ishii et al ., 2009; Otowa et al ., 2009; Konishi et al ., 2014; Han et al ., 2015; Zou et al ., 2019; Wang et al ., 2020; Yang et al ., 2021; Chu et al ., 2022), involving 2203 cases and 2554 controls. The flow chart of literature selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 31 articles were selected for full‐text assessment. Finally, 12 articles met the inclusion criteria and were included (An et al., 2019 ; Carlino et al., 2015 ; Chen et al., 2022 , 2017 ; Chu et al., 2022 ; Kim et al., 2019 ; Kobayashi et al., 2005 ; Li et al., 2023 ; Maron et al., 2009 ; Molendijk et al., 2012 ; Ströhle et al., 2010 ; Wang et al., 2020 ) (see Figure 1 for the PRISMA flow diagram).…”
Section: Resultsmentioning
confidence: 99%
“…The qualitative synthesis revealed heterogeneity in terms of study design, BDNF measurement methods, and panic disorder severity measures. Recent studies reported lower BDNF protein levels in individuals with panic disorder compared to healthy controls (Chu et al, 2022;Li et al, 2023;Wang et al, 2020). However, there were some discrepancies among the findings, with some studies reporting no significant differences (An et al, 2019;Carlino et al, 2015;Chen et al, 2017Chen et al, , 2022Kim et al, 2019;Kobayashi et al, 2005;Molendijk et al, 2012) or even higher BDNF levels in individuals with panic disorder (Maron et al, 2009).…”
Section: Qualitative Synthesismentioning
confidence: 99%